Overexpression of a bHLH1 Transcription Factor of Pyrus ussuriensis Confers Enhanced Cold Tolerance and Increases Expression of Stress-Responsive Genes - Jin, Cong; Huang, Xiao-San; Li, Kong-Qing; Yin, Hao; Li, Lei-Ting; Yao, Zheng-Hong; Zhang, Shao-Ling (Frontiers in Plant Science, 2016)
Abstract The basic helix-loop-helix (bHLH) transcription factors are involved in arrays of physiological and biochemical processes. However, knowledge concerning the functions of bHLHs in cold tolerance remains poorly understood. In this study, a PubHLH1 gene isolated from Pyrus ussuriensis was characterized for its function in cold tolerance. PubHLH1 was upregulated by cold, salt and dehydration, with the greatest induction under cold conditions. PubHLH1 had the transactivational activity and localized in the nucleus. Ectopic expression of PubHLH1 in transgenic tobacco conferred enhanced tolerance to cold stress. The transgenic lines had higher survival rates, higher chlorophyll, higher proline contents, lower electrolyte leakages and MDA when compared with WT. In addition, transcript levels of eight genes associated with ROS scavenging, regulation, and stress defense were higher in the transgenic plants relative to the WT under the chilling stress. Taken together, these results demonstrated that PubHLH1 played a key role in cold tolerance and, at least in part, contributed to activation of stress-responsive genes.